If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+13/4=2
We move all terms to the left:
x+13/4-(2)=0
determiningTheFunctionDomain x-2+13/4=0
We multiply all the terms by the denominator
x*4+13-2*4=0
We add all the numbers together, and all the variables
x*4+5=0
Wy multiply elements
4x+5=0
We move all terms containing x to the left, all other terms to the right
4x=-5
x=-5/4
x=-1+1/4
| 8+4k=28 | | 3(j+21)=90 | | -4.9t^2+10t=-80 | | 2u+30=66 | | 2x+9=1x+-3 | | 5x-8/x+2=5-6/x-2 | | 2b+5=b+6 | | 50x-3x=x-26 | | 3+m=27 | | -4.9t^2+10t=80 | | 3x+7x-2=3x-7x+2 | | 2x-13+x=122 | | 26x+2+x+20x=180 | | 2(x-3)+3x+7=2x+19 | | 16x+6+11x+6+x=180 | | 9x^2–18=7 | | 36=-9(n-98) | | 20(x–11)=–20 | | 48,797+11.25x=23,541+18.25x | | 7x+4+9x+x=180 | | -11=16-(-9r) | | 52-u=8 | | 37+98+x=180 | | 0.5+2=6x-64 | | 1=t-89/6 | | 5x-8/x=2=5-6/2x | | 3(v-62)=51 | | 3x²-6x+27=0 | | 8x+9=41+4x | | 2(x-2)+4x=-16 | | 2(3x-2)=4(x-2) | | 0.60x=60+0.10 |